Research on rotating high-frequency current injection method based on LC resonance network. (30th November 2020) - Zhong, Li-Ping
The high-frequency signal injection method is an effective method to realise the sensorless detection of the rotor position of the permanent magnet synchronous motor (PMSM), which can estimate any position of the rotor in the whole speed range. When the frequency of the injected signal is high, the rotating high-frequency current injection method can obtain more significant signal with rotor position information for PMSM with small salient characteristics, so it can obtain higher position estimation accuracy. However, the traditional method of injecting high-frequency current needs current source inverter or complex control mode, which is difficult to apply in practice. The drive circuit based on LC resonant network can convert the resonant voltage signal into the current signal, thus the driving voltage and rotating high-frequency current signals can be simultaneously provided to the PMSM through the voltage source inverter, which greatly facilitates the extraction and processing of rotor position information and improves the sensorless detection accuracy of rotor position. The experimental results verified the effectiveness of the circuit and method.